Pengembangan Kurikulum Pendidikan Agama Kristen: Transformasi Dan Adaptasi Untuk Era Modern - Mutiara Meylan Simorangkir; Monika Gultom; Damayanti Nababan (MAN Insan Cendekia Jambi, 2025)
The development of a Christian Religious Education (PAK) curriculum is crucial in ensuring the relevance and effectiveness of learning in the contemporary era. This study examines various aspects of PAK curriculum development using a qualitative approach through literature review. The results indicate that PAK curriculum development must consider biblical, theological, philosophical, historical, educational, psychological, and sociological foundations. Transforming the PAK curriculum requires technology integration, 21st-century skills development, and a holistic approach to prepare students for future challenges. An effective PAK curriculum must be able to bridge Christian values with the demands of modern education, while maintaining Christian identity and characteristics.